Acute psychosis followed by fever – Malignant neuroleptic syndrome or viral encephalitis? - Stojanović, Zvezdana; Špirić, Željko (Vojnosanitetski pregled, 2014)
Introduction. Neuroleptic malignant syndrome is rare, but potentially fatal idiosyncratic reaction to antipsychotic medications. It is sometimes difficult to diagnose some clinical cases as neuroleptic malignant syndrome and differentiate it from the acute viral encephalitis. Case report. We reported a patient diagnosed with acute psychotic reaction which appeared for the first time. The treatment started with typical antipsychotic, which led to febrility. The clinical presentation of the patient was characterised by the signs and symptoms that might have indicated the neuroleptic malignant syndrome as well as central nervous system viral disease. In order to make a detailed diagnosis additional procedures were performed: electroencephalogram, magnetic resonance imaging of the head, lumbar puncture and a serological test of the cerebrospinal fluid. Considering that after the tests viral encephalitis was ruled out and the diagnosis of neuroleptic malignant syndrome made, antipsychotic therapy was immediately stopped. The patient was initially treated with symptomatic therapy and after that with atypical antipsychotic and electroconvulsive therapy, which led to complete recovery. Conclusion. We present the difficulties of early diagnosis at the first episode of acute psychotic disorder associated with acute febrile condition. Concerning the differential diagnosis it is necessary to consider both neuroleptic malignant syndrome and viral encephalitis, i.e. it is necessary to make the neuroradiological diagnosis and conduct cerebrospinal fluid analysis and blood test. In neuroleptic malignant syndrome treatment a combined use of electroconvulsive therapy and low doses of atypical antipsychotic are confirmed to be successful.
Keywords: neuroleptic malignant syndrome; encephalitis; viral; diagnosis; differential; treatment outcome